Changes in ec, ph and in the concentrations of nitrate, ammonium, sodium and chlorine in the drainage solution of a crop of roses on substrates with drainage recycling (2012)
The rose cultivation system has been changing from soil to substrate on the Plateau of Bogota. The objective of this study was the monitoring of the EC, pH, and the levels of nitrate, ammonium, sodium and chlorine in a drainage solution in a crop of roses with substrates based on burnt rice husk and coconut fiber. The Charlotte rose variety grafted onto ‘Natal Briar’ was planted in a greenhouse located in one of the SENA facilities in Mosquera (Colombia); with a density of 6.5 plants/ m2. For this experiment, a split plot design was used arranged in randomized blocks with a three-level recirculating system (0, 50 and 100%) on the substrates 100% burnt rice husk; 65% burnt rice husk plus 35% coconut fiber; and 35% burnt rice husk plus 65% coconut fiber, repeated three times. The EC decreased from 2.7 to 1.3 mS cm-1 within weeks 2 and 5 which demonstrated an increase of mineral consumption by the plants. The pH levels dropped from 7.46 to 6.27 within weeks 3 to 8 and then increased to 7.39 within weeks 8 to 12. Nitrate concentrations showed a decreasing trend in recirculation treatments within weeks 2 to 12. A lower ammonium concentration was observed at week 4 in treatments with and without recirculation during the vegetative stage. The levels of sodium and chloride increased in treatments with recirculation, without signs of toxicity.